Pengenalan Sayur dan Buah untuk Anak Autis berbasis Multimedia Augmented Reality - Sri Lestari; Sutarman Sutarman; Saucha Diwandari (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Autism is a neurobiological developmental disorder that affects the social, communication, and interaction abilities of children. Difficulty accepting and interacting with healthy foods, such as vegetables and fruits, is a common challenge for children with autism. To address this challenge, researchers propose the use of augmented reality (AR) technology as an interactive and enjoyable method to introduce vegetables and fruits to children with autism. This study aims to investigate the effectiveness of using AR in increasing the interest and acceptance of vegetables and fruits in children with autism by suggesting the use of augmented reality technology and applying the Picture Exchange Communication System (PECS) technique. The PECS method is a communication training technique that uses pictures or symbols to assist children with autism in communication. This application is designed using the Unified Modelling Language (UML) tools. Testing of this application is conducted through alpha and beta testing. The results of alpha testing using black box testing conclude that the application runs smoothly without any functionality issues. The results of beta testing, with an average of 82.50%, suggest that the use of the PECS method and AR technology can enhance communication skills and motivation in introducing vegetables and fruits and can help children with autism follow a gluten-free casein-free (GFCF) diet to reduce the symptoms experienced by children with autism.